Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$\ln(x + 1) = 2 + \ln(x - 1)$; solve for $x$.

From there I get $$\ln \frac{x+1}{x-1} = 2.$$

Am I headed in the right direction, in our examples we would exponentiate both sides, does that still stand for this even though there's only a 2 on the right hand side?

share|improve this question
1  
Yes, you get $e^2$ on the right... –  J. M. Dec 6 '11 at 16:12
1  
Yes, you are doing well. After a short while you will get a linear equation for $x$. –  André Nicolas Dec 6 '11 at 16:12
2  
Yes, you are in the right direction. Now take exponentials on both sides to eliminate the $\ln$. –  Arturo Magidin Dec 6 '11 at 16:13
3  
Minor comment: The subtraction is fine of course, but myself I would prefer to take the exponential immediately, get $x+1=(e^2)(x-1)$. –  André Nicolas Dec 6 '11 at 16:23

3 Answers 3

up vote 4 down vote accepted

You are right. From

$$\ln \frac{x+1}{x-1} = 2.$$

we can write it as

$$e^{\ln \frac{x+1}{x-1}}=e^{2} $$

then

$$\frac{x+1}{x-1}=e^{2}$$

You can find the solution for $x$

share|improve this answer

Why not take the exponential of both sides immediately? We get $$x+1=(e^2)(x-1),$$ and it's over.

share|improve this answer
1  
That would be a better way to do it. Most College Algebra texts I've seen have you "collect the logs" first. I suppose the authors want to give the student practice using the rules of logarithms. –  David Mitra Dec 6 '11 at 16:39
    
That would be correct David, as we just went over the rules of logs the previous week. –  erimar77 Dec 6 '11 at 16:44

Yes, you use the fact that $$\ln u=v\iff u=e^v.$$ So applying this to what you have (with $u={x+1\over x-1}$ and $v=2$): $$ \tag{1}{x+1\over x-1}=e^2. $$ Multiplying both sides by $x-1$ gives $$ \tag{2}x+1=e^2(x-1). $$ (note, here that $x=1$ is not a solution of (2); so (1) and (2) are equivalent equations)

Solving for $x$ in (2):

$$\eqalign{ &x+1= e^2 x-e^2\cr &\iff x-e^2x =-1-e^2\cr &\iff x(1-e^2)=-1-e^2\cr &\iff x= {-1-e^2\over 1-e^2} } $$ Or $$ x={e^2+1\over e^2-1}. $$

When solving logarithmic equations, you sould always check your answers. In particular, check that you don't wind up taking the logarithm of a non-positive quantity.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.